Efficacy and safety profile of long‐term exposure to lenalidomide in patients with recurrent multiple myeloma. Issue 20 (6th August 2013) - Fouquet, Guillemette; Tardy, Stéphanie; Demarquette, Hélène; Bonnet, Sarah; Gay, Julie; Debarri, Houria; Herbaux, Charles; Guidez, Stéphanie; Michel, Jessica; Perrot, Aurore; Serrier, Caroline; Miljkovic, Darko; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Lenalidomide in combination with dexamethasone (Len/Dex) is indicated for patients with recurrent/refractory multiple myeloma (RRMM) who were treated with 1 prior therapy until evidence of disease progression. The objective of the current study was to determine the efficacy and safety profile of long‐term exposure to Len/Dex. METHODS A total of 50 patients with RRMM who were treated with long‐term Len for ≥ 2 years from 2 Intergroupe Francophone du Myélome (IFM) centers (Lille and Nancy) were included in the current study. RESULTS The median age of the patients was 58 years, with 30% of the patients aged > 65 years, 49% having an International Staging System stage of 2 and 3, 12% having severe renal insufficiency, and 8% demonstrating an adverse result on fluorescence in situ hybridization. Approximately 56% of the patients received treatment with Len/Dex for ≥ 3 years. The median duration of treatment with Len/Dex was 3 years (range, 2 years‐7 years). The response rates for partial response or better and very good partial response or better for the overall cohort were 96% and 74%, respectively, which is similar to patients exposed to Len for ≥ 3 years. With a median follow‐up of 4 years, 19 (38%) patients had stopped treatment with Len/Dex. The time to disease progression rate at 37 months was 78% and 91%, respectively, in patients exposed to Len for 2 years to < 3 years and for ≥ 3 years (P = 025). The safety profile was manageable, similar to that of Len when administered for a shorter period of time; 16% of patients had grade 3 to 4 neutropenia, 6% had thrombopenia, 6% had anemia, and 20% experienced thromboembolic events, all of venous type. The annual incidence rate of second primary malignancy was 1.96% in the current series. CONCLUSIONS The results of the current study confirmed that the Len/Dex combination is feasible for long‐term use in patients with RRMM, with a significant benefit noted in terms of time to disease progression for prolonged treatment with Len/Dex. Cancer 2013;119:3680–3686. © 2013 American Cancer Society.